Akibat Hukum Tidak Membentuk Perhimpunan Pemilik Dan Penghuni Satuan Rumah Susun - Mahmoud, Arief Rahman; Suhariningsih, Suhariningsih; Koeswahyono, Imam (Jurnal Mulawarman Law Review, 2019)
This article aims to determine legal consequences and remedies not filling the provisions of article 74 paragraph 1 of law number 20 year 2011 jo article 54 paragraph 1 of government regulation number 4 of 1988 concerning the association of the occupants unit of flats, using normative legal research methods, through approach to legislation, conceptual and comparison in order to obtain the views an doctrines as a basis legal arguments on legal issues studied. Based on the survey result revealed that, with no formation of associations of occupant flats units, then the resident will lose the right to enjoy a sense of comfort, easy, safe, orderly and organized the principles in the flats. According to article 107 flats legislation may be subject to adminisrative sanctions contained in article 108 of the law enactment flats in stages, ranging from a written warning to revocation of business license. Remedies that can be given the resident can do prosecution by first reporting to the local authorities for further prosecution to the developer. According article 75 paragraph 1 law flats: ”development actors are required to facilitate the formation of associations occupant apartment units at the latest before the transitional period ends. In article 59 paragraph 2”. The transitional period a maximum of one year since the first delivery of flats units to the owner.